Sebuah Respons Kristen terhadap Penggunaan Aplikasi Clubhouse di Era Covid-19 - Carmia Margaret; David Alinurdin (Reformed Center for Religion and Society, 2021)
Some Recent discussions about the reality of virtual space show that virtual space can mediate the presence between subject and create meaningful relationships. This article intends to test the realization of this idea in a virtual communication room, called Clubhouse which has been a trending topic discussion Clubhouse is a voice-based on social media application that users can connect directly without text, images, photos, or videos. Initially, Clubhouse was opened only as an invitation application, but recently this application can be accessed freely by all internet users without invitation. If the Clubhouse application is read as a “cultural text,” it will reflect values that intersects with the Biblical principles, namely about exclusivity and inclusivity also the element of self-giving in a relationship. Through this reading, Clubhouse is considered as an alternative to have a relationship if its user is balanced with the creation of contexts or conditions that ensure users’ awarness and make deliberate efforts to their existence and optimize the fulfillment of mental images through various traces of presence.